Role of Probation and Social Welfare Office in Mitigating the Effects of Child Neglect on Children’s Social Well-Being in Upper Kauga, Mukono District - Kelly Lambda Mangeni (Uganda Christian University, 2024)
Young adults leave foster care between the ages of 18 and 21 depending on their country of residence. Now the transition from foster care to independent living presents significant experiences for watoto young adults. Having potentially experienced neglect, trauma and instability in their childhoods, these young adults find it hard to establish themselves financially, emotionally and socially as independent adults. Understanding their experiences is crucial for improving their outcomes. In this study, the primary aim was to explore the experiences of young adults transitioning out of watoto foster care program through examining the strategies employed by watoto to help young adults secure stable employment as they seek independence, exploring the housing experiences of young adults during their first year after leaving the program, and exploring the primary health care needs of those who have transitioned out of the watoto care system. This study utilized a qualitative case study design to understand the in depth of the experiences of young adults transitioning out of watoto foster care in Uganda. The study employed purposive sampling, a non-randomized technique to recruit participants who met the specific criteria relevant to the research question. In this study, a qualitative data analysis was obtained through guided interviews and focused group discussions. It is outstanding to note that from our findings Watoto child care ministries as a well-designed system for its foster care that plans for the childs entry and final exit in this we noted that a childs basic needs approach is very essential in there activity plan .they law out how a child will meet all their basics and also make it in time to come for example we were pleased to note that a child has a place to call home ,parents to call mothers and siblings in those homes they also go ahead to have gentlemen to be role model fathers( called the fathers heart program ) for every house that visit and have a chat with the childrens welfare and so much more. With the health care, housing and strategies put in place to secure stable employment its also evident enough that Watoto has played its part by this I mean that many of the program former fosters have made it big places in the market place some are lawyers, bankers, social workers working for Uganda in different departments or even back at watoto to give their skills in the different departments. Another outstanding factor was that even after the foster care one has built a very big support system in and outside always a call away in times of need which becomes family for further mentorship and support as Research suggests that youth in foster care who have natural mentors during adolescence have improved young adult outcomes. Connections to non-parental adults through informal mentoring is reported to enhance the outcomes of foster care youth in education/employment, psychological well-being, and physical health. Youth who had the support of a mentor also demonstrated a decreased participation in unhealthy behaviors, such as unprotected sexual activity, alcohol and substance abuse, and delinquent activities and with this Watoto has out done its self-children or adult youths have support on standby to support them throughout.
Postgraduate research